Pengaruh Pupuk Organik Cair Terhadap Pertumbuhan Kedelai (Glycine max (L.) Merr) pada Tanah Podzolik Merah Kuning - Zein, Anizam; Leilani, Irma (Lembaga Penelitian Universitas Negeri Padang, 2008)
The research of the effect of liquid organic fertilizer to the soybean growth on podzolik merah kuning soil has been held. The aim of the research is to know the effect of fluid organic fertilizer to he growth of soybean on podzolik merah kuning soil. This research is complete randomized design (RAL) about this research in 6 treatment and 4 repetation. Those are A = 0 ml/polibag, B = 60 ml/polibag, C = 120 ml/polibag, D = 180 ml/polibag, E = 260 ml/polibag, F = 300 ml/polibag. The data is analyzed by various investigation and continued test with DMRT. The result of research shows that it’s giving the positive effect of soil’s pH, the plant’s heigh, plants aged 7, 14, 21, 28, nd 35 days number of leaves, total wet weight’s plant, dried weight’s plant and number of nodule of these plants shows positive effect of the soybean’s growth. Key word : Soybean, liquid organic fertilizer, growth